Faktor-faktor Keputusan Muzakki untuk Berzakat Melalui Lembaga Amil Zakat: Studi pada BAZNAS Provinsi Kepulauan Bangka Belitung - Fitri Yanti; Hatamar Hatamar; Reno Ismanto (JYRS: Journal of Youth Research and Studies, 2023)
Technological advances have had many positive impacts on the development of zakat management. Especially in terms of increasing transparency, accountability and service quality. These three aspects are considered to have an impact on increasing the number of muzakki in Zakat Institutions, including the National Amil Zakat Agency (BAZNAZ). This study seeks to analyze the relationship between these three aspects on the decision to become muzakki with zakat at the National Zakat Amil Agency (BAZNAS) in the Bangka Belitung Islands Province. The population of this study is 518 people, with a sample of 84 respondents. The data obtained were analyzed using multiple regression tests and hypothesis testing using SPSS version 26.0. as an analytical tool. The research results show that, partially, Transparency, Accountability and Service Quality have a significant effect on Muzakki's decision to pay zakat at BAZNAZ Bangka Belitung Islands Province. Simultaneously, these three variables also show the same results. The Study also shows that three variables contribute a portion of 10.5% factors of decision to become muzakki, while the rest are influenced by other variables not examined in this study.